X^3 - 3x^2 + 5x - 15
x^2(x-3) +5(x-3)
(x^2 + 5)(x - 3) <==Answer
Let z = 3x+2. Then, by substitution, your equation is
.. z^2 +7z -8 = 0
_____
This equation can be factored as
.. (z +8)(z -1) = 0
.. x = -8 or +1
Then
.. 3x +2 = -8 or +1
.. 3x = -10 or -1
.. x = -10/3 or -1/3
Answer:
Step-by-step explanation:
<span>The number can be 102, 108, or 114. They can all be formed that way.
32 + 34 + 36 = 102
34 + 36 + 38 = 108
36 + 38 + 40 = 114
</span>The n<span>ext one is 120 . . . . . 38 + 40 + 42</span>